2D MODELLING OF THE GAS FLOW STRUCTURE IN THE SYMBIOTIC STAR Z ANDROMEDAE - Kilpio, E. Yu. (Одеські астрономічні публікації, 2017)
The 2D gasdynamical simulations of gas structure in the symbiotic star Z And have been carried out for different stellar wind regimes. Since the mechanisms of gas acceleration in stellar atmospheres are not well studied, the parametric representation of gas accelerating force was used. The calculations for various stellar wind velocity regimes have shown that for realistic cases the accretion discs in the system were formed.